Defectos refractivos y su influencia en el desempeño académico de los estudiantes de octavo y noveno de educación básica de la Unidad Educativa Miguel Ángel Samaniego Jiménez Babahoyo -Los Ríos. Diciembre 2022-mayo 2023. - Ramos Burgos, Johana Vicenta (2023)
Introduction: The work has the need to investigate the refractive errors that influence their academic performance. These visual problems affect students in their ability that affects the achievement of their objectives. Objective: To analyze the refractive defects in the academic performance of the students of the eighth and ninth year of basic education of the Miguel Ángel Samaniego Jiménez Educational Unit, Babahoyo canton. Methodology: the deductive and inductive method was applied, a cross-sectional field study. In the field because the area where the research is directed is observed, the review of the medical records of the students was used as a technique, the transversal modality was also used because a group of students was observed and certain data obtained in a study were also analyzed. certain moment. Results: visual exams were performed on each student. 13 have myopia corresponding to 86%, 2 students have myopic astigmatism corresponding to 13%. Of the 24 students who were evaluated, 62% of these visual problems affect their academic performance. Conclusions: most of the students valued in this study present 86% myopia and 13% myopic astigmatism. Refractive errors are one of the main factors that affect the quality of vision of students, negatively affecting academic performance.